Influence of the Crystallinity on the Physicochemical Properties of Spray-Dried Quercetin-Inulin Microparticles and Their Performance During in Vitro Digestion - Gimenez-Castillo, B (Elsevier Ltd, 2024)
Encapsulation of quercetin (Q) with inulin (In) by spray-drying was performed applying a Box-Behnken design where the effect of the inlet air temperature, percentage of inulin crystallite dispersion and Q content were studied on the crystallinity index (CI). Three microparticle systems with CI between 2 % and 20 % (Q-In-2 %, Q-In-12 % and Q-In-20 %) were selected to study the CI effect on Q release during an in vitro digestion. The higher the CI of microparticles, the higher the encapsulation efficiency (76.4 %, Q-In-20 %). Surface quercetin was steadily released during the oral, gastric, and intestinal phases of the digestion. The CI of the microparticles did not influence the Q bioaccessibility values (23.1–29.7 %). The highest Q delivery occurred during the simulated colonic phase (44.4–66.4 %) due to the action of the inulinase. The controlled crystallization in spray-dried microparticles is a promising strategy for the designing of polyphenol-based microparticles with specific delivery properties. © 2023 Elsevier Ltd